THE INFLUENCE OF ORGANIZATIONAL CITIZENSHIP BEHAVIOUR ON EMPLOYEE PERFORMANCE AT PT ANANDA PERKASA MULIA - Nurdin (JURNAL ASIK, 2025)
The purpose of this study was to determine the influence of organizational citizenship behavior on employee performance at PT Ananda Perkasa Mulia. The research method used in this research is descriptive with a quantitative approach. The sampling technique used saturated samples so that the number of samples in this study was 60 respondents. Data analysis technique using multiple regression. The results of the study show that: There is a positive and significant influence of the organizational citizenship behavior on the employee performance at PT Ananda Perkasa Mulia. This is evidenced by the value of tcount > ttable, namely 9,588 > 2,001 with a probability value (significance) = 0,000, which is below 0.05.